Complex Post-Traumatic Stress Disorder and Child Abuse - Fowler, Omolayo; Oladeji, Oluwatoyin; Nkemjika, Stanley; bansal, Sourav (International Journal of Psychosocial Rehabilitation, 2022)
Child abuse is a global challenge with long-term detrimental effects on children’s development, growth, and functions. Several studies have highlighted the impact of childhood exposure to abuse on developing complex interruptions of neurosequential and neurological deficits linked to physical and mental health issues. Complex post-traumatic stress disorder is an interpersonal trauma that starts in early life with profound psychopathological effects. Studies have revealed that the survivors of traumatic events present complicated symptoms such as psychiatric disorders such as antisocial personality disorders, dissociation, substance abuse, sexual disorders, somatoform, eating and affective disorders, and health issues. This review was mostly about how the hypothalamic-pituitaryadrenal axis, the hippocampus, the amygdala, and the prefrontal cortex are involved in the link between child abuse and the development of complex post-traumatic stress disorder.